Study of FPGA Based Vector Control of Induction Motor - Srinivas, G. (New Approaches in Engineering Research Vol. 16, 2021)
The controller implementation for the generation of PWM signals is critical to obtaining the desired response of the sensor less Vector controlled Induction Motor (SVC-IM) by the experimental setup. With the rapid growth of the electronic industry, such as high speed digital signal processors (DSPs) with microcontrollers available these days, it is possible. Previously, DSP technologies were used to implement the various SVC-IM schemes, namely KF, PI, GA, and PSO. It causes problems related to the time delay and execution of the PWM signals, etc., as a results system becomes complex. As a result, a new approach is implemented to address the issue of execution time, namely Field Programmable Gate Array (FPGA) processors, which are currently being proposed in the market. Furthermore, the programming is done in VHDL, which is a very high-speed hardware descriptive language.